Rice Marketing Channels - Nurhalisa Nurhalisa; Helviani Helviani; Masitah Masitah; Nursalam Nursalam; Bustang Bustang (Agribusiness Journal, 2023)
Puudongi Village is one of the villages which is a rice production center in Tanggetada District, Kolaka Regency. The marketing problems faced by farmers in marketing their rice yields are due to the lack of information about the price level of rice in the market. So that the price of rice at the farm level is easily manipulated by marketers. This study aims to determine the rice marketing channel in Puudongi village, Polinggona sub-district, to find out the size of the price share received by farmers (farmer share) from rice marketing activities in Puudongi village, Polinggona sub-district, to find out how much the rice marketing margin is in Puudongi village, Polinggona sub-district and to determine the efficiency of rice marketing channels in the village of Puudongi, Polinggona District. Based on the results of marketing channel research, there are two marketing channels. For farmer share (the share of prices received by farmers) shows that marketing channel II with farmer's share (FS) is 95.2%, marketing channel I is with farmer's share (FS) 88.3%. Paddy marketing margin in channel I is IDR 500/kg while channel II is IDR 200/kg.